Hiding in plain sight: Gastric mass as a herald of angioimmunoblastic T‐cell lymphoma. Issue 5 (1st September 2020) - Adams, Michael B.; Foster, Daniel V.; Fenderson, Joshua L.; Gonzales, Paul; Thompson, Misty; Rosa, Cesar J.
Abstract: Background/study aims: Angioimmunoblastic T‐cell Lymphoma (AITL) is a rare T‐cell lymphoma often presenting with constitutional symptoms and lymphadenopathy. It can have an association with Epstein‐Barr Virus (EBV) infection and auto‐immune phenomena such as haemolytic anaemia. This case details a Gastric Mass as the initial findings of AITL, a rare occurrence. Patients and methods: Case report detailing a 64‐year‐old female presenting with a suspicious gastric mass and auto‐immune haemolytic anaemia. Hospital workup was notable for serology consistent with acute EBV infection and positive anti‐smooth muscle antibody. Tissue biopsy and lymph node resection yielded histologic diagnosis of AITL. Results: Once the patient was diagnosed with AITL, they were placed on Gemcitabine, Cisplatin, Prednisone and Thalidomide with subsequent improvement in haemolytic anaemia and gastric mass size. Conclusions: This case demonstrates a unique presentation of Angioimmunoblastic T‐cell Lymphoma in the context of a Gastric Mass and associated Auto‐immune Haemolytic Anaemia. This case also continues to show evidence of a strong relationship between Epstein‐Barr Virus and Angioimmunoblastic T‐cell Lymphoma.